2006
DOI: 10.1124/dmd.105.008227
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein and an Unstirred Water Layer Barring Digoxin Absorption in the Vascularly Perfused Rat Small Intestine Preparation: Induction Studies with Pregnenolone-16α-carbonitrile

Abstract: ABSTRACT:Digoxin, a substrate of P-glycoprotein (Pgp) and cytochrome P450 3a (Cyp3a), was used to illustrate the inductive effects of pregnenolone-16␣-carbonitrile (PCN), a ligand of the pregnane X receptor, on the absorption and disposition of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
5
34
0
Order By: Relevance
“…We have noted that heterogeneity models such as the SSFM and STM (Tam et al, 2003), whether necessary or not, are more pertinent in cases of enzyme heterogeneity among the segments. In absence of metabolism by the intestine, we found that the STM and SSFM perform as well as the TM and SFM, as found for studies on the absorption of benzoic acid (Cong et al, 2001) and digoxin absorption and efflux by P-gp (Liu et al, 2006) in the vascularly perfused intestine preparation. The presence of metabolite data is an absolute necessity for the discrimination between the SFM and TM.…”
Section: Intestinal Flow Models In Pbpk Modelingsupporting
confidence: 61%
See 2 more Smart Citations
“…We have noted that heterogeneity models such as the SSFM and STM (Tam et al, 2003), whether necessary or not, are more pertinent in cases of enzyme heterogeneity among the segments. In absence of metabolism by the intestine, we found that the STM and SSFM perform as well as the TM and SFM, as found for studies on the absorption of benzoic acid (Cong et al, 2001) and digoxin absorption and efflux by P-gp (Liu et al, 2006) in the vascularly perfused intestine preparation. The presence of metabolite data is an absolute necessity for the discrimination between the SFM and TM.…”
Section: Intestinal Flow Models In Pbpk Modelingsupporting
confidence: 61%
“…2 for various drugs range from 2.4, 5.7, 8.6, to 16.6 l/h, corresponding to 6.5 to 43% of the total intestinal flow, with good predictions for midazolam but poor estimation of F I (or F G ) for saquinavir in vivo . Some of these f Q values for the Q Gut model are higher than the f Q values of 0.07, 0.024, and 0.2 estimated from fits of the SFM to the data on benzoic acid (Cong et al, 2001), morphine (Cong et al, 2000), and digoxin (Liu et al, 2006), respectively, from vascularly perfused rat small intestine preparations. For digoxin, which is mainly excreted unchanged in the mouse in vivo, a value of 0.16 was found for f Q (Chow et al, 2011).…”
Section: Comparison Of F Qmentioning
confidence: 85%
See 1 more Smart Citation
“…The emergence of the Q Gut model (Yang et al, 2007) and the advanced dissolution, absorption, metabolism model from Simcyp (Darwich et al, 2010) favors this concept of partial flow. Other models that further encompass heterogeneity in transporters and enzymes have been adopted to explain the lesser intestinal metabolism observed for drugs given systemically versus orally (Tam et al, 2003;Liu et al, 2006;Bruyère et al, 2010;Gertz et al, 2010) as well as the effect of enterohepatic circulation of glucuronide conjugates (Wu, 2012). Undoubtedly, our PBPK investigation strongly supports the SFM for intestinal modeling.…”
supporting
confidence: 57%
“…It has been reported that the expression level and activity of P-450 isozymes are decreasing along with the length of the small intestine from the duodenum to the ileum (de Waziers et al, 1990;Liu et al, 2006). However, the distribution of CES isozyme has not been determined yet.…”
Section: Resultsmentioning
confidence: 94%